Robotic ureteral reconstruction for recurrent strictures after prior failed management. Issue 3 (16th February 2023) - Lee, Matthew; Lee, Ziho; Houston, Nicklaus; Strauss, David; Lee, Randall; Asghar, Aeen M.; Corse, Tanner; Zhao, Lee C.; Stifelman, Michael D.; Eun, Daniel D.; ,
Abstract: Objectives: To describe our multi‐institutional experience with robotic ureteral reconstruction (RUR) in patients who failed prior endoscopic and/or surgical management. Materials and Methods: We retrospectively reviewed our Collaborative of Reconstructive Robotic Ureteral Surgery (CORRUS) database for all consecutive patients who underwent RUR between 05/2012 and 01/2020 for a recurrent ureteral stricture after having undergone prior failed endoscopic and/or surgical repair. Post‐operatively, patients were assessed for surgical success, defined as the absence of flank pain and obstruction on imaging. Results: Overall, 105 patients met inclusion criteria. Median stricture length was 2 (IQR 1–3) centimetres. Strictures were located at the ureteropelvic junction (UPJ) (41.0%), proximal (14.3%), middle (9.5%) or distal (35.2%) ureter. There were nine (8.6%) radiation‐induced strictures. Prior failed management included endoscopic intervention (49.5%), surgical repair (25.7%) or both (24.8%). For repair of UPJ and proximal strictures, ureteroureterostomy (3.4%), ureterocalicostomy (5.2%), pyeloplasty (53.5%) or buccal mucosa graft ureteroplasty (37.9%) was utilized; for repair of middle strictures, ureteroureterostomy (20.0%) or buccal mucosa graft ureteroplasty (80.0%) was utilized; for repair of distal strictures, ureteroureterostomy (8.1%), side‐to‐side reimplant (18.9%), end‐to‐end reimplant (70.3%) or appendiceal bypass (2.7%) was utilized. Major (Clavien >2) post‐operative complications occurred in two (1.9%) patients. At a median follow‐up of 15.1 (IQR 5.0–30.4) months, 94 (89.5%) cases were surgically successful. Conclusions: RUR may be performed with good intermediate‐term outcomes for patients with recurrent strictures after prior failed endoscopic and/or surgical management.